Una propuesta alternativa a la concepción del llamado capital humano = Incorporation of sociological and axiological elements to the process of individuals' formation - Odriozola Guitart, Silvia‏ (Textos & Contextos (Porto Alegre), 2013)
The theory of human capital, in spite of its great universal acceptance, has been criticized from diverse perspectives. However, in not few occasions it is assimilated with insufficient reflections on its deeper significance. It is not about criticizing the human capital term; neither about redefining it. It is about breaking up with the logic of thought of the theory that sustains it (the logic of thought of the neoclassical theory) and to formulate a new conception that includes the notions about the individual’s formation and their importance for the progress of the society, from the free, universal and emancipating development of the human beings. In this sense, a non-excluding and emancipating society cannot limit the role of human beings to their function in the productive process. It should rather consider their active and conscious participation in the transformation of the reality, for the sake of their full and universal development. There for the need to advance in alternative proposals that overcome the narrowness of the merely economic considerations that sustains the theory of the human capital, starting from the incorporation of sociological and axiological elements to the process of individuals' formation